2020
DOI: 10.1177/0040517520935212
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the total within-sample variation in cotton fiber length using the High Volume Instrument fibrogram

Abstract: Within-sample variation in cotton fiber length is important when explaining variation in yarn quality. However, typical High Volume Instrument (HVI) length parameters, the Upper Half Mean Length (UHML) and Uniformity Index (UI), do not characterize the total within-sample variation in fiber length. HVI fiber length measurements are based on the fibrogram principle where the HVI generates a curve called a fibrogram and reports the UHML and UI. Our results, based on 19,628 commercial bales, reveal that the typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 29 publications
0
26
0
2
Order By: Relevance
“…A qualidade da fibra é aferida mediante a classificação visual e análise laboratorial, mediante o uso do Instrumento de Alto Volume (High Volume Instrument -HVI) e outros complementares (SAYEED et al, 2021). Por meio do HVI são analisadas características da fibra como Resistência (STR), Comprimento (UHML), Micronaire (Finura da fibra), SFI (Índice de fibras curtas), Alongamento (ELG), Maturidade (MR), RD (Refletância/Brilho/grau de cinza), +B (Grau de amarelamento), Thash Folha (Grau de impureza).…”
Section: Revisão De Literaturaunclassified
See 1 more Smart Citation
“…A qualidade da fibra é aferida mediante a classificação visual e análise laboratorial, mediante o uso do Instrumento de Alto Volume (High Volume Instrument -HVI) e outros complementares (SAYEED et al, 2021). Por meio do HVI são analisadas características da fibra como Resistência (STR), Comprimento (UHML), Micronaire (Finura da fibra), SFI (Índice de fibras curtas), Alongamento (ELG), Maturidade (MR), RD (Refletância/Brilho/grau de cinza), +B (Grau de amarelamento), Thash Folha (Grau de impureza).…”
Section: Revisão De Literaturaunclassified
“…A tecnologia de enfardamento em rolos cilíndricos permite que a colhedora realize uma colheita contínua sem interrupções para descarregamento do algodão colhido. O resultado codificado da análise laboratorial é posteriormente informado na etiqueta do fardo onde consta a sigla HVI (High Volume Instrumentequipamento utilizado para medir as características intrínsecas da fibra do algodão), consoante Sayeed et al (2021). Esse resultado será fundamental no processo de valoração da pluma, bem como no emprego correto pela indústria têxtil, sendo destinada tanto para o mercado interno quanto externo.…”
Section: Metodologiaunclassified
“…The coded result of the laboratory analysis is later reported on the bale label with the acronym HVI (High Volume Instrument -equipment used to measure the intrinsic characteristics of cotton fiber), according to Sayeed, Schumann and Wanjura (2021). This result will be fundamental in the lint valuation process, as well as in the correct use by the textile industry, being destined for both domestic and foreign markets.…”
Section: Fig9: Smart Box 45 Press Bale Labeling and Transport To Storagementioning
confidence: 99%
“…Fiber quality is assessed by visual classification and laboratory analysis using the High-Volume Instrument (HVI) and other complementary instruments (Sayeed, Schumann, & Wanjura, 2021). Through the HVI, fiber characteristics such as Strength (STR), Length (UHML), Micronaire (Fiber fineness), SFI (Short Fiber Index), Elongation (ELG), Maturity (MR), RD (Reflectance/Brightness/Grayness), +B (Yellowing degree), Thash Sheet (Impurity degree) are analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been some investigation of the fibrogram produced by the HVI to potentially extract additional length parameters. In 2020, Sayeed et al 13 demonstrated that the current UHML and ML are highly correlated with the 1.8% and 7.8% span lengths, respectively (R 2 ¼ 0.99 for both). These two span lengths represent the longest part of the fibrogram, as shown in Figure 2, and were shown to be highly correlated with each other (R 2 ¼ 0.95).…”
mentioning
confidence: 99%